Effect of different dates of sowing on pearl millet (Pannisetum glaucum L.) hybrids under semi-arid region of Rajasthan: Effect of sowing date on pearl millet yield - M.L. Reager, M.L. Reager; Subhash Chandra; Kishor, Naval; B.S. Kherawat; Richa Pant (Annals of Arid Zone, 2023)
Millet produces high quality grains than any other cereals under extreme conditions of unfertile soil, intense heat and prolong drought. An experiment was conducted during the Kharif season of 2021and 2022 at Krishi Vigyan Kendra, Bikaner-II (Lunkaransar), Swami Keshwanand Rajasthan Agricultural University, Bikaner, with the treatment combination of three date of sowing (15th, 30th July and 15th August) and seven hybrids of pearl millet (HHB-67 improved, HHB-197, HHB-299, MPMH-17, HHB-273, HHB-226 and BHB-1602). The experiment was laid out in split plot design with three replications. The pooled result reveled that yield attribute, yield, Net returns and B:C Ratio (benefit cost ratio) were recorded significantly higher in the first sowing date (15th July) statistically showed maximum seed yield (21.19 qt ha-1), Net Return (30086 Rs ha-1) with B:C ratio (2.72) followed by second date of sowing (30th July) seed yield (17.51qt ha-1), Net Return (22356 Rs ha-1) with B:C ratio (2.28) and third date of sowing (15th August) seed yield (11.08 qt ha-1), Net Return (8824 Rs ha-1) with B:C ratio (1.50) respectively. Similarly, hybrid MPMH-17 recorded significantly higher grain yield 19.69 qt ha-1 followed by hybrid HHB-299 (18.62 qt ha-1), HHB-273 (16.90 qt ha-1), HHB-197      (16.74 qt ha-1), HHB-67 (15.51 qt ha-1), HHB-226 (14.42 qt ha-1) and BHB-1602 (14.28 qt ha-1) respectively. The highest seed yield 26.06 qt ha-1and Net Returns (40358 Rs ha-1) was recorded in hybrid MPMH-17 on first date of sowing (15th July) which was statistically at par with sowing 30th July.